Asymmetric ratio and FCM based salient channel selection for human emotion detection using EEG - Mohamad Rizon, Mohamed Juhari; Murugappan, M.; Ramachandran, Nagarajan; Sazali, Yaacob (World Scientific abd Engineering Academy and Scoiety (WSEAS), 2009)
Link to publisher's homepage at http://www.worldses.org